The impact of very high gravity fermentation conditions on brewing yeast health and physiology - Alexander, Chris (2022)
As modern industrial efforts shift towards more economic and sustainable practices, the brewing industry is no different. Namely, the application of high gravity (HG) and very high gravity (VHG) brewing practices provide the means to increase brewery efficiency and reduce energy input. However, the conditions experienced throughout VHG fermentations exert an increased degree of stress on the fermenting yeast population, resulting in poor ethanol yields, impaired yeast quality and unbalanced beer flavour. The aim of this research was to investigate the influence of stress factors experienced by yeast during fermentation on yeast physiology and key quality indicators.